Impact of Hurricane Maria on Beach Erosion in Puerto Rico: Remote Sensing and Causal Inference. Issue 6 (10th March 2020) - Pérez Valentín, Jaynise M.; Müller, Marc F.
Abstract: Beach erosion due to large storms critically affects coastal vulnerability, but is challenging to monitor and quantify. Attributing erosion to a specific storm requires a reliable counterfactual scenario: hypothetical beach conditions, absent the storm. Calibrating models to construct counterfactuals requires numerous observations that are rarely available. Storm paths are unpredictable, making long‐term instrumentation of specific beaches costly. Optical remote sensing is hampered by persistent cloud cover. We use Sentinel‐1 satellite radar imagery to monitor shoreline changes through clouds and propose regression discontinuity as a strategy to estimate the causal effect of large storms on beach erosion. Applied to 75 beaches across Puerto Rico, the approach detects shoreline changes with a root‐mean‐square error comparable to the resolution of the imagery. Hurricane Maria caused an erosion of 3 to 5 m along its path, up to 40 m at particular beaches. Results reveal strong local disparities that are consistent with simulated nearshore hydrodynamic conditions. Key Points: Hurricane Maria caused immediate beach loss of 3 to 5 m in Puerto Rico, with very large local disparities Sentinel 1 synthetic aperture radar (SAR) can accurately monitor shoreline changes in cloudy conditions Causal attribution of beach erosion to a specific storm is achieved using a regression discontinuity approach